Regaining Iceland for the Catholic Church in the mid-19th Century - Birgir Guðmundsson; Markus Meckl (The University of Akureyri, 2014)
In the late 1850s, the Church of Rome sent missionaries to Iceland; to begin with, a Catholic priest and an assistant. The proclaimed purpose of their stay was to service the thousands of French seamen that were fishing for cod in Icelandic waters. However, although the official and most visible purpose of the Catholic mission was to attend to the French sailors, the mission was also meant to reclaim Iceland to the Catholic faith. This essay contains the first account of the experiences of father Bernard, the priest who was in charge of this mission.